HASIL DESTILASI KERING DAN NILAI KALOR KAYU NANGKA (Artocarpus heterophyllus Lamk) - Sri Komarayati; Djeni Hendra (Pusat Penelitian dan Pengembangan Hasil Hutan, 1994)
Rapid destructive of Jackfruit wood was carried out by using a retort equipped with electrical heating system. This retort was also connected to a condensor and two flask to catch and collect the distillate or condensed gas. The retort capacity was about 4 kg of wood. Treatment conditions given in these experiment were maximum heating temperature of 500◦ C and 5 hours distillation time.The results showed that charcoal yield of Jackfruit wood varied from 25.00 to 39.81%, tar from 6.23 to 9.42% and pyroligneous liquor from 67.64 to 102.05%. The calorific value of wood varied from 4392.00 to 4620.65 kcal/g and charcoal from 6691.81 to 7108.37 kcal/g.Based on these calorific values, wood and charcoal of Jackfruit wood are excellent material for fuel.